Microbiological Safety of Leafy Vegetables Produced at Houeyiho and Sèmè-Kpodji Vegetable Farms in Southern Benin: Risk Factors for Campylobacter spp. - Sylvain Daton Kougblénou; Alidéhou Jerrold Agbankpé; Justin Gbèssohélé Béhanzin; Tamègnon Victorien Dougnon; Alidah Victonie Aniambossou; Lamine Baba-Moussa; Honoré Sourou Bankolé (International Journal of Food Science)
Foodborne infections, mainly those attributable to Campylobacter, are one of the most common causes of intestinal diseases, of bacterial origin in humans. Although the vehicle of transmission is not always identified, the most common vehicles are poultry, poultry products, and contaminated water. In Southern Benin, an excessive use of poultry manure as fertilizer in vegetable farms was noted. This survey aimed to determine the prevalence and concentration of Campylobacter spp., especially Campylobacter jejuni and Campylobacter coli, in selected environmental samples (poultry manure, and irrigation water) and freshly harvested leafy vegetables in two (Houeyiho and Sèmè-Kpodji) vegetable farms in southern Benin. To achieve this objective, we analyzed 280 samples, including 224 samples of leafy vegetables (Solanum macrocarpon and Lactuca sativa capita), 28 samples of irrigation water, and 28 samples of poultry manure. The analysis of the samples taken was carried out according to the modified NF EN ISO 10272-1 standard. Of the 280 samples analyzed in this survey, 63 were positive for Campylobacter contamination. For leafy vegetable samples analyzed in this survey, the contamination rate was of 15.63%. 60.71% of poultry manure samples analyzed were contaminated with Campylobacter spp. and 39.29% of irrigation water samples were contaminated. The statistical analysis of these results showed that there is a correlation between the contamination of leafy vegetables, poultry manure, and irrigations (p<0.01). Campylobacter jejuni (53.97%) was more involved in contaminations than Campylobacter coli (36.57%). This study has shown that there is a real risk of food poisoning by Campylobacter jejuni and Campylobacter coli among consumers of leafy vegetables in southern Benin. The origin of contamination of these leafy vegetables is poultry manure used as fertilizer in vegetable gardens and irrigation water used.